Cardiometabolic Risk in Stunted Children: A Literature Study - Brigitte Sarah Renyoet; Ilmia Fahmi (Jurnal Penelitian Pendidikan IPA, 2025)
Global health and nutrition are undergoing an epidemiological transition with the emergence of the "Triple Burden of Malnutrition," which includes undernutrition, obesity, and micronutrient deficiencies. Children experiencing stunting are at high risk for long-term cardiometabolic diseases, including cardiovascular disease and diabetes. However, longitudinal studies exploring the relationship between stunting and cardiometabolic risk are still limited. This study aims to identify and examine the relationship between stunting in children and the associated cardiometabolic risks and evaluate interventions implemented to reduce these risks. A literature review approach was conducted by analyzing 22 research articles focusing on children aged 0-5 years with stunting status. Inclusion criteria included evaluating cardiometabolic risks such as hypertension, diabetes, and dyslipidemia. The literature search followed PRISMA guidelines and utilized PubMed, ScienceDirect, and Google Scholar databases. The research indicates that stunting significantly impacts the risk of cardiometabolic issues in the future. Early nutritional interventions, such as protein-energy supplementation and ongoing dietary counseling, have effectively reduced these risks; however, socioeconomic factors often influence their effectiveness. Addressing stunting should be a priority in preventing long-term health risks. A holistic approach is needed, integrating nutritional, health, and social aspects to tackle this issue, particularly in low- and middle-income countries.